The Function of Trademark and Legal Protection for MSME's in the Covid-19 Era: Fungsi Merek dan Perlindungan Hukum bagi Pelaku UMKM di Era Covid-19 - Ratih Agustin Wulandari; Raimon Efendi (Perkumpulan Doktor Indonesia Maju, 2020)
The free trade system requires UMKM to be able to compete, and made this moment to be able to introduce the best UMKM products in the global market. In the current era of global trade, the emergence of counterfeiting or piracy often appears, for this reason, legal protection is needed for Intellectual Property Rights, especially for UMKM over brands. The purpose of this study was to determine the function of the brand and legal protection provided by the State of the brand for UMKM. The research method used in this research is the method of legal sociology which is an approach that analyzes how reactions and interactions occur when the norm system works in society. The results of this study are the first Brand Function provides legal protection for business people, UMKM products will be better known to people, consumers' trust in their products will increase, can create personality, help promotion. Legal protection of trademarks based on Law Number 20 of 2016 concerning brands and geographical indications, legally protected marks are registered trademarks, protection is also in the form of civil damages or compensation. Legal protection for brands is also in the form of preventive and regrentive legal protection.